MODERN CHALLENGES IN THE FIELD OF EDUCATION: ETHICAL ASPECTS OF USING ARTIFICIAL INTELLIGENCE THROUGH THE EYES OF STUDENTS - Михеєва, Тамара; Євтух, Артем (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
The article examines the ethical challenges that arise in the process of introducing artificial intelligence (AI) technologies into the educational space, in particular through the eyes of students. The author analyzes the experience of using AI in the training of higher education students, with special attention paid to ethics, the development of practical skills and the impact of technology on the educational process. Based on the concept of the trajectory of AI integration into the educational environment, the key areas of its implementation in the educational process are identified, including personalization of learning, motivational support and development of meta-skills. Particular attention is paid to the legal aspects of the ethical use of AI, in particular, the problems of intellectual property protection and regulation of innovations. The purpose of the article is to empirically investigate the ethical aspects of using artificial intelligence in education and science from the perspective of students. Objectives of the study: to analyze the experience of using AI in the training of higher education students; to analyze the model of the trajectory of integration of artificial intelligence into the educational environment; to consider the legal aspects of the ethical use of AI; to conduct an empirical study on the ethical aspects of using AI in education and science from the perspective of students. To achieve this goal, the following research methods were used: scientific analysis, systematization, generalization, comparison, and questionnaire. Results: the article analyses the experience of using AI in the training of higher education students and the model of the trajectory of artificial intelligence integration into the educational environment; considers the legal aspects of the ethical use of AI and conducts an empirical study on the ethical aspects of using AI in education and science from the perspective of students. Conclusions. The results of the empirical study showed a high level of integration of AI into students' learning activities, in particular for information retrieval, text editing, planning, or idea generation. At the same time, a number of ethical challenges have been identified: an unclear distinction between acceptable and unacceptable forms of AI use, the “shifting” of moral responsibility from the user to AI technologies, and a low level of legal awareness of copyright and academic integrity.